2019
DOI: 10.1261/rna.072454.119
|View full text |Cite
|
Sign up to set email alerts
|

HNRNPH1-dependent splicing of a fusion oncogene reveals a targetable RNA G-quadruplex interaction

Abstract: The primary oncogenic event in ∼85% of Ewing sarcomas is a chromosomal translocation that generates a fusion oncogene encoding an aberrant transcription factor. The exact genomic breakpoints within the translocated genes, EWSR1 and FLI1, vary; however, in EWSR1, breakpoints typically occur within introns 7 or 8. We previously found that in Ewing sarcoma cells harboring EWSR1 intron 8 breakpoints, the RNA-binding protein HNRNPH1 facilitates a splicing event that excludes EWSR1 exon 8 from the EWS-FLI1 pre-mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 67 publications
(90 reference statements)
4
36
0
Order By: Relevance
“…Computer modeling has hinted that G:H π–π interactions are vital for aligning and binding RNA transcripts to the b-subunit of RNA polymerases ( 29 ), while CD72 uses several Y residues to form π–π interactions with RNA nucleobases in order to act as a regulatory protein for B lymphocytes ( 30 ). In the absence of structural data, π–π stacking between the RNA-binding protein heterogeneous nuclear ribonucleoprotein H1 (HNRNPH1) and an RNA G-quadraplex has been proposed to be related to alterative splicing and the onset of cancer ( 31 ). Although the RNA and protein components are anticipated to be relatively co-planar in the previous examples, nonparallel nucleobase–amino acid binding modes also occur.…”
Section: Introductionmentioning
confidence: 99%
“…Computer modeling has hinted that G:H π–π interactions are vital for aligning and binding RNA transcripts to the b-subunit of RNA polymerases ( 29 ), while CD72 uses several Y residues to form π–π interactions with RNA nucleobases in order to act as a regulatory protein for B lymphocytes ( 30 ). In the absence of structural data, π–π stacking between the RNA-binding protein heterogeneous nuclear ribonucleoprotein H1 (HNRNPH1) and an RNA G-quadraplex has been proposed to be related to alterative splicing and the onset of cancer ( 31 ). Although the RNA and protein components are anticipated to be relatively co-planar in the previous examples, nonparallel nucleobase–amino acid binding modes also occur.…”
Section: Introductionmentioning
confidence: 99%
“…One aspect of this and subsequent studies highlighted the dependency of about one‐third of Ewing sarcomas that harbor chromosome 22 translocations in intron 8 of the 5ʹ partner gene, EWSR1 . Specifically, our work demonstrated that EWS cells harboring EWSR1 ‐intron 8 breakpoints depend on the RNA binding protein HNRNPH1 to generate the in‐frame protein‐coding fusion mRNA in these tumor cells 107,108 …”
Section: Unraveling the Miswiring Of Cancer Signalingmentioning
confidence: 84%
“…The last G4 structure included in this group is found in the EWS RNA binding protein 1, EWSR1 , one of the genes most commonly involved in sarcoma translocations, rendering novel transcription factors with tumoral effects [ 145 ]. EWSR1 mRNA contains a parallel-tetramolecular G4 structure within exon 8, which enables the recruitment of HNRNPH1, a component of the heterogeneous nuclear ribonucleoprotein (hnRNP) complex required for the processing of distinct EWSR1 transcript variants [ 57 ].…”
Section: Relevant Quadruplex Structures Involved In Cancermentioning
confidence: 99%
“…For instance, the well-known cationic porphyrin TMPyP4 acts as a general stabilizer of quadruplexes including DNA [ 167 ] and RNA G4s [ 168 ], but also i-Motifs [ 169 ]. The same occurs with the pan-quadruplex binding molecule, Pyridostatin, which binds to all quadruplex structures [ 57 , 170 , 171 ]. In the case of BRACO-19, it shows binding affinity for both DNA G4s [ 172 ] and i-Motifs [ 170 ].…”
Section: Therapeutic Relevance Of Quadruplex Structures In Cancermentioning
confidence: 99%